Histone deacetylase inhibitors for the treatment of breast cancer: recent trial data. (June 2013) - Truong, Thach-Giao; Munster, Pamela
Epigenetic modification has recently been recognized as an important factor in the development of therapy resistance in cancer. Hence, histone deacetylase inhibitors as potential epigenetic modifiers are an emerging class of novel cancer therapeutics and have been extensively studied. Here, we review the role of histone deacetylase inhibitors in the treatment of breast cancer as single agents as well as in combination with chemotherapeutic, hormonal, and targeted agents.